Bizantyńska poezja liturgiczna na wybranych przykładach VI-IX wieku - Heszen, Agnieszka (Vox Patrum, 2026)
This article presents the interdependence of hymnography and Byzantine liturgy in the period from the sixth to the ninth century. The texts preserved in the liturgical books associated with the period of Lent and Holy Week and songs included in the books of the Menaia were examined in order to show the functioning of hymns in the different liturgical cycles, the annual variable and the stable one of the memories of the saints. Excerpts from Romanos Melodos’ kontakions On the Ten Maidens and On the Harlot were compared with Kassia’s the Nun troparion dedicated to the same figure, followed by several stanzas from the Great Penitential Canon of Andrew of Crete with the Canon for Holy Saturday, by Kassia. The troparion On Basil the Great was selected from the book Menaia. This juxtaposition of poetic genres, intended for mornings or vespers liturgy, made it possible to look at the liturgical functions of the hymns, their structure, structure and poetics, subordinated to the services celebrated, and at the same time constructed in an elaborate literary form. The article combines issues of liturgy with philological and literary analysis and demonstrates the importance of extant liturgical books for the study of Christian hymnography.